Pemberdayaan Masyarakat melalui Pemanfaatan Limbah Sekam Padi sebagai Pemeliharaan Kesehatan Lingkungan di Desa Gambut - Chandra, Chandra; Rahman, Eddy; Asrinawaty, Asrinawaty; Indah, Meilya Farika; Agustina, Norsita (Jurnal Abdimas Kesehatan (JAK), 2025)
Gambut Village, Banjar Regency, the average person works as a farmer. This of course makes Peat Village get the slogan "Kindai Limpuar" which generates a lot of moneyWaste Waste - Rice residue or what we commonly call rice husks. With the result of rice husks thatThis abundance is one of the opportunities to improve the creative economy and also protect the environment in the community so that  there is zero waste by making charcoal which can later be traded at a fairly high price. Charcoal from Rice Husk Waste is a type of biomass that is very easy to use and utilize. The purpose of the community empowerment program in making charcoal from rice husk waste is to provide training and assistance to farmers in the Peat Village work area to process agricultural waste so that it becomes a useful product in the form of rice husk charcoal. and improve the creative economy of the people there. The method used in this service is training and assistance in making charcoal from rice husk waste. The result of this service activity is a bracket product / husk charcoal derived from rice husk which is expected from this product, one of which can reduce the rate of environmental pollution due to careless disposal of husk waste in the area so that from this community service activity from counseling and training to peatland farmers can have a positive impact. The training that has been carried out can increase farmers' knowledge and skills in utilizing rice waste to be processed into husk charcoal.  Rice husk agricultural waste, which was previously considered a problem, becomes useful after good and correct management. Farmers' dependence on chemical fertilizers can be slightly reduced.